The Relationship between Estimated Glomerular Filtration Rate and Diabetic Retinopathy - Jingyang Wu; Jin Geng; Limin Liu; Weiping Teng; Lei Liu; Lei Chen (Journal of Ophthalmology)
Diabetic retinopathy (DR) is the leading cause of visual impairment and blindness in working-aged people. Several studies have suggested that glomerular filtration rate (GFR) was correlated with DR. This is a hospital-based study and the aim of it was to examine the relationship between the GFR and DR in patients with type 2 diabetes mellitus (T2DM). We used CKD-EPI equation to estimate GFR and SPSS 19.0 and EmpowerStats software to assess their relationship. Among the 1613 participants (aged 54.75 ± 12.19 years), 550 (34.1%) patients suffered from DR. The multivariate analysis revealed that the risk factors for DR include age (P<0.001, OR = 0.940), duration of diabetes (P<0.001, OR = 1.163), hemoglobin A1c (P=0.007, OR = 1.224), systolic blood pressure (P<0.001, OR = 1.032), diastolic blood pressure (P=0.007, OR = 0.953), high density lipoprotein cholesterol (P=0.024, OR = 3.884), and eGFR (P=0.010, OR = 0.973). Through stratified analysis and saturation effect analysis, our data suggests that eGFR of 99.4 mL/min or lower might imply the early stage of DR in diabetic patients. Thus, the evaluation of eGFR has clinical significance for the early diagnosis of DR.